Por que a Globo Matou a Globeleza? O Silenciamento da Globo em Relação às Polêmicas Sobre Racismo e Nudez nas suas Vinhetas de Carnaval - Silva, Carlos (Mulheres no Discurso - Women in Discourse, 2025)
The proposed work aims to analyze the silencing and unspoken aspects in the statements issued by Globo to the press regarding the controversy over the absence of the Globeleza muse in 2023 and the debates surrounding racism and nudity in the carnival vignettes. To support the proposed discussions, the study draws on the ideas of Orlandi in the books Discourse Analysis: Principles and Procedures (2003) and The Forms of Silence (1995), as well as Maingueneau (2008), along with contributions from other authors to explore the unspoken or silencing, discursive ethos, and issues of gender and race in the vignettes. The research methodology includes a literature review and French discourse analysis based on Pêcheux (Orlandi, 2003). The findings suggest that the broadcaster, in its discourse, silences the controversies involving its brand, instead focusing its statements and modes of expression on the plurality of Brazil's carnival.